Kinning With The Unseen More-Than-Human: Re-Sensing Barrambin's Disappeared Waterways And Creeks For Community Connection To Place - Turner, Jane; Seevinck, Jen; Foth, Marcus; Armstrong, Keith; Vickery, Nicole; Kelly, Nick; Tyurina, Anastasia; McKinnon, Heather; Low, Amari; Davies, Lowana (Australian Council of University Art and Design Schools (ACUADS), 2022)
We present collaborative research and design processes emerging through endeavours to engage with relational ontologies in place [1]. The aim is to reveal stories and reconnect the local community with the hidden habitats, more-than-human inhabitants and latent significance of a Brisbane waterway. The project is being developed for a local grove and waterway area – a cultural site for the Turrbal and Yuggera First Nations People and now a residential village and part of a university teaching campus. Historically the locality was rich in fresh water with a billabong, pools and small creeks leading down to wetlands and the Brisbane river. As a pathway to the river, the area had cultural significance from gatherings and corroborees but has undergone many incarnations: quarry, squatter’s camp, army rifle-range and, recently, golf course. The new village was built with its back to the waterway. Recent flooding events have however revealed this significant aspect of place and community. Our project seeks to re-appear and re-make place and meaning, providing an opportunity to reconnect the village communities and visitors with Barrambin and its stories. Our design process focuses on discovering a relationship – kinning [2] – with these disappeared (unseen) waterways. We draw on creative workshops, speculative design and data visualisation methods to playfully and ethically engage with community and develop possibilities for connecting and revealing the long-forgotten waterways underneath. This approach to place-making as movement ‘between’ [3] resonates with wider university and city strategies, potentially offering both bridges and local interlocutors to the enmeshed view of Country that these other developments are embodying. Kinning provides a theoretical framework to pursue social and sustainable design intervention, bringing environmental action to the fore while relating to conference themes. Kinning also demands that we re-frame our methodologies to work within relational ontologies or risk perpetuating the ...